2012
DOI: 10.9753/icce.v33.currents.24
|View full text |Cite
|
Sign up to set email alerts
|

Barred-Beach Morphological Control on Infragravity Motion

Abstract: A conceptual analysis of the coupling between bars and infragravity waves is performed combining laboratory experiments and numerical modeling. Experiments are carried out in a wave flume with a barred profile. The Boussinesq fully-nonlinear model SERR1D is validated with the laboratory data and a sensitivity analysis is performed next to study the influence on the infragravity wave dynamics of bar amplitude and location, and swash zone slope. A novel technique of incident and reflected motions separation that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…These results put in perspective the use of these relations to estimate the nearshore energy budget. They also strongly support the idea of a key feedback of swash on surf zone hydro-morphodynamics, particularly with regards to the potential influence of this on sandbar dynamics (Almar et al, 2012), even if no clear evidence has been obtained yet, mainly due to the paucity of observations.…”
Section: Discussionsupporting
confidence: 67%
“…These results put in perspective the use of these relations to estimate the nearshore energy budget. They also strongly support the idea of a key feedback of swash on surf zone hydro-morphodynamics, particularly with regards to the potential influence of this on sandbar dynamics (Almar et al, 2012), even if no clear evidence has been obtained yet, mainly due to the paucity of observations.…”
Section: Discussionsupporting
confidence: 67%
“…Variables such as water saturation on the swash zone, infragravity waves and the energy transfer from the high to the low frequency, standing waves patterns (see ALMAR et al, 2012), and so on, should be taken into account. Moreover, variation of bed…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the processes associated to the energy transfer between short and long waves and beach reflection remains a research challenge, but the last is crucial to understand how the swash zone affects the long wave behavior, the standing wave patterns and the interaction with the morphology (MASSELINK & PULEO, 2006). For example, recent studies using laboratory and numerical data (ALMAR et al, 2012) have shown the major control of swash slope on the outgoing reflected wave as well as on the standing long wave pattern, being the swash a low frequency filter in which the flatter the beach the lower frequency of the outgoing component. Moreover, the impact of individual swash events is still poorly addressed.…”
mentioning
confidence: 99%
“…At the steepest beaches and in the case of long period waves, observations show that up to 60-80% of the incoming wave energy is reflected (Battjes, 1974;Elgar et al, 1994). Reflected waves can strongly influence and interact with incident waves; change individual wave shape (Abdelrahman and Thornton, 1987;Rocha et al, 2017), intensify undertow (Martins et al, 2017), and generate standing or even resonant waves (Almar et al, 2012;. This effect on the hydrodynamics is thought to have a feedback on submerged morphological bed forms (e.g.…”
Section: Introductionmentioning
confidence: 99%